Pengaruh Nilai Persediaan, Profit Margin, Metode Arus Biaya Persediaan dan Return On Equity Terhadap Market Value - Herpika Oktavia; Andrian Noviardy (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This study aims to provide information about the factors that affect the company's market value. In this research, the writer examines "The Influence of Inventory Value, Profit Margin, Inventory Cost Flow Method and Return On Equity on Market Value". The object used in this study is the food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2018-2021. It is known that the number of companies in the food and beverage sub-sector is 26 companies, by looking at the predetermined criteria there are 15 companies that are suitable to be used as samples. The data analysis method used is multiple linear regression analysis.